Credit constraints, energy management practices, and investments in energy saving technologies: German manufacturing in close-up - Andreas Löschel; Benjamin Johannes Lutz; Philipp Massier (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
We analyze the drivers and barriers that influence investments increasing the energy efficiency of firms' production processes or buildings in the German manufacturing sector based on microdata. In particular, we shed light on the relationship between financial barriers (e. g. credit constraints), information and knowledge (e. g. energy management practices), salience of energy-related topics, and the investments in energy saving technologies. A better understanding of firms' investment behavior regarding energy saving technologies is crucial to design efficient policy measures, which are necessary to achieve the imposed ambitious climate and energy policy targets. We use data from 701 structured telephone interviews in combination with commercial and confidential firm-level data. Our results suggest that energy management practices have a statistically significant positive relationship with investment decisions on energy saving technologies for production processes and buildings. Credit constraints are a barrier to investments in the energy efficiency of firms' production processes. Furthermore, high energy cost shares of heating or cooling, high energy intensity, energy self-generation and structured internal decision making processes influence the investments in energy efficiency positively.
urn:nbn:de:bsz:180-madoc-439744
Keywords: D22; H23; Q41; Q48; Q58; 330; Energy efficiency; Credit constraints; Energy management; Manufacturing; industry; Investment behavior